2019
DOI: 10.1038/s41598-019-48305-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in IgE sensitization associated with alcohol consumption in the general population

Abstract: The association of alcohol consumption and immunoglobulin E (IgE) sensitization is debated. Few population-based studies have investigated whether such associations differ by sex. We explored the association of alcohol consumption with IgE sensitization in the general population, stratified by sex. We analyzed data for 1,723 adults from the 2010 Korean National Health and Nutrition Examination Survey. We divided subjects into three groups according to their self-reported alcohol consumption or serum level of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Peripheral blood samples were collected after fasting for more than eight hours, and then were immediately processed and transported to a central laboratory (Neodin Medical Institute, Seoul, South Korea). All blood samples were analysed within 24 h after collection 48 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripheral blood samples were collected after fasting for more than eight hours, and then were immediately processed and transported to a central laboratory (Neodin Medical Institute, Seoul, South Korea). All blood samples were analysed within 24 h after collection 48 .…”
Section: Methodsmentioning
confidence: 99%
“…Regular exercise was defined as moderate physical activity performed for at least 30 min at a time at least five times a week. Height, weight, and waist circumference were measured by trained medical professionals 48 .The body mass index (BMI) was calculated as body weight (kg) divided by height in meters squared (m 2 ) 49 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different mechanisms, about how microbiota may influence and regulate the innate and adaptive immune responses with emphasis on the Th2 pathway, have been reviewed in detail in our previous AllergoOncology Position Paper [110]. One study showed that germ-free mice have elevated total IgE levels, resulting Age [164] Childcare [165] Gender [92,94] Number of siblings [166] Race [95] Socio-economic status [95] Allergen immunotherapy [167] Corticosteroids [103] Dupilumab [102] Ligelizumab [101] Omalizumab [99] Rituximab [168] Air pollution [169] Microbiota [110,112] Smoking [166] Vitamin D level [ • Due to current minimal information in the field, we cannot specify screening tests or establish recommendations for patients with IgE deficiency. However, with the goal of understanding the role of diminished IgE in the general population, certain clinical findings (e.g.…”
Section: Microbiota Influences On Ige Levelsmentioning
confidence: 99%
“…Two previous longitudinal studies reported that physical activity was not associated with asthma incidence among middle-aged and older women [11, 12], whereas a Finnish cohort study showed that physical activity had a protective effect on asthma onset in men [10]. Furthermore, previous studies have indicated the possibility of sex differences in the effects of smoking and drinking on asthma development [13, 14], but the available population-based studies are insufficient, particularly for older people.…”
Section: Introductionmentioning
confidence: 99%